Alvar Aalto : Designer - Olafsdottir, Asdis; Mikonranta, Kaarina (Jyväskylä : Alvar Aalto Museum Alvar Aalto Foundation, 2002)
Focus op meubelontwerpen en andere objecten voor het interieur van de Finse architect Aalto
Engels
boek
Keywords: Aalto, Alvar; Artek; Iittala; Karhula Glassworks; 1898 - 1976; eigen tijd; Finland